Electrocatalysts based on low amounts of palladium combined with tin nanoparticles and cerium dioxide nanorods for application as ADEFC anodes - Pinheiro, Victor S.; Souza, Felipe M.; Gentil, Tuani C.; Nascimento, Aline N.; Parreira, Luanna S.; Hammer, Peter [UNESP]; Sairre, Mirela I.; Batista, Bruno L.; Santos, Mauro C. (Elsevier, 2021)
This study demonstrates the structural properties and evaluates the electrocatalytic activity of an ethanol oxidation reaction using ternary materials composed by Pd and Sn nanoparticles combined with CeO2 nanorods (NR) anchored on Vulcan carbon black to be used as an anode in alkaline direct ethanol fuel cells (ADEFCs). The highest open circuit voltage (1010 mV), maximum power (30 mW cm−2) and current densities (113 mA cm−2) were achieved using (Pd1Sn3)10(CeO2 NR)20(Vn)70, while the commercial anode values were 968 mV, 23 mW cm−2 and 123 mA cm−2. Although similar performance for both anodes was observed, the ternary hybrid electrocatalyst contains an 8-fold lower Pd content than the commercial material. This outcome may be justified by the higher defect density presented by the carbon support observed by Raman spectroscopy and the metal oxidation state modifications detected by X-ray photoelectron spectroscopy, as well as the electrochemically active surface area presented by the ternary electrocatalyst. The combination of higher vacancies, defects and oxygenated species in the carbon support and the synergistic effect between the oxyphilic Sn and CeO2 NR species and the Pd nanoparticles results in an electrochemical performance that makes these ternary electrocatalysts promising anode materials for ADEFC applications.
Keywords: Alkaline direct ethanol fuel cells; Ceria nanorods; Ethanol oxidation reaction; Hybrid electrocatalysts; Palladium; Sn-containing electrocatalysts